The loss of Java the final battles for the possession of Java fought by allied air, naval, and land forces in the period of 18 February-7 March 1942 - Boer, P. C. 1948- (NUS Press, 2011)
Explains in detail the air, sea and land battles between the Allied and Japanese armed forces during the battle for Java that followed the evacuation of southern Sumatra in February 1942